The Model of the Early Central European State and the Pre-Christian Grand Duchy of Lithuania - Babinskas, Nerijus (History / Istorija, 2022)
Abstract. The concept of the early Central European state has been elaborated for decades in the historiographies of neighboring countries but has so far been ignored in the Lithuanian medievalist literature. The author makes an attempt to base the thesis that the concept mentioned before is an original contribution of Central European historians to the comparative historical sociology of pre-capitalist peripheral societies. Furthermore, its application to the interpretation of the socio-political and socioeconomic structure of the early medieval Grand Duchy of Lithuania might offer original theoretical insights and provide an opportunity for Lithuanian medievalists to become involved in international comparative research as well as reinvigorate theoretical discussions.